Birth outcomes in a Swedish population of women reporting a history of violence including domestic violence during pregnancy: a longitudinal cohort study - Hafrún Finnbogadóttir; Kathleen Baird; Li Thies-Lagergren (BMC, 2020)
Abstract Background Victimisation of women is encountered in all countries across the world, it damages the mental and physical health of women. During pregnancy and the postpartum period, women are at a greater risk of experiencing violence from an intimate partner. The aim of this study was to explore childbirth outcomes in a Swedish population of women reporting a history of violence including domestic violence during pregnancy. Methods A longitudinal cohort design was used. In total, 1939 pregnant women ≥18 years were recruited to answer two questionnaires, both questionnaires were administered in the early and late stages of their pregnancy. The available dataset included birth records of 1694 mothers who gave birth between June 2012 and April 2014. Statistical analyses included descriptive statistics, T-test and bivariate logistic regression. Results Of 1694 mothers 38.7% (n = 656) reported a history of violence and 2% (n = 34) also experienced domestic violence during pregnancy. Women who were single, living apart from their partner, unemployed, smoked and faced financial distress were at a higher risk of experiencing violence (p = 0.001). They also had significant low scores on the SOC-scale and high EDS-scores ≥13 (p = 0.001) when compared to women without a history of violence (p = 0.001). Having a history of violence increased the woman's risk of undergoing a caesarean section (OR 1.33, 95% CI 1.02-1.70). A history of emotional abuse also significantly increased the risk of having a caesarean section irrespective of whether it was a planned or an emergency caesarean section (OR 1.50, 95% CI 1.09-2.06). Infants born to a mother who reported a history of violence, were at significant risk of being born premature < 37 weeks of gestation compared to infants born by mothers with no history of violence (p = 0,049). Conclusions A history of violence and/or exclusively a history of emotional abuse has a negative impact on childbirth outcomes including caesarean section and premature birth. Therefore, early identification of a history of or ongoing violence is crucial to provide women with extra support which may have positive impact on her birth outcomes.